Efektivitas Media Pembelajaran Bertukar Tiket Dalam Mata Pelajaran Matematika Pada Materi Operasi Penjumlahan dan Penguranganbilangan Positif dan Negatif Terhadap Hasil Belajar Siswa Kelas IV di SD Negeri 064976 Bandar Selamat - Agnes Mutika Kirana Br Barus; Futri Pratiwi Munthe; Sri Sintya Lovyanda Sitanggang; Zahwa Nirwana Dwi Ningsi Hamidy (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
This research was conducted with the aim of increasing students' understanding of the operations of adding and subtracting positive and negative numbers using exchanging positive and negative tickets in mathematics subjects at SD Negeri 064976 Bandar Selamat. In this research, the necessary data was produced using collection techniques, namely observation, interviews with students and conducting tests on students. Based on the results of the research carried out, significant results were found, namely an increase in student learning outcomes whose learning outcomes were better than before.